2006
DOI: 10.1111/j.1365-3016.2006.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Collecting population‐based perinatal data efficiently: the example of the Lebanese National Perinatal Survey

Abstract: We describe the methodology and the main results of the Lebanese perinatal health survey. The survey was carried out during two consecutive weeks in autumn 1999 and spring 2000, with the aim of obtaining a minimum data set on all births occurring during a short period of time. All live births and stillbirths occurring during these periods in medical settings were recorded. The sample included 5231 women and 5333 newborns. Data were obtained from medical records and by interviewing the women in hospital after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…The control mothers educational levels were very similar to those of the French population, but the control fathers' educational levels were higher. [22][23][24] However, parental socioeconomic status and educational level were not associated with a family history of cancer in the control group and the results were unchanged after adjustment for these variables. We collected no direct information on ethnicity, which might be related to the risk of childhood cancer and to history of cancer in relatives.…”
Section: Discussionmentioning
confidence: 74%
“…The control mothers educational levels were very similar to those of the French population, but the control fathers' educational levels were higher. [22][23][24] However, parental socioeconomic status and educational level were not associated with a family history of cancer in the control group and the results were unchanged after adjustment for these variables. We collected no direct information on ethnicity, which might be related to the risk of childhood cancer and to history of cancer in relatives.…”
Section: Discussionmentioning
confidence: 74%
“…This probably explains at least in part the higher rate of such deliveries in France (11.1% in 2003) compared with the US (6.6% in 2006) (22,23). Previous studies have reported an association between PPH and operative vaginal delivery (24).…”
Section: Discussionmentioning
confidence: 79%
“…Elle met en communication la cavité amniotique et les germes de la flore cervicovaginale. C'est une situation fré quente repré sentant 8 % des grossesses et impliqué e dans 30 % des accouchements pré maturé s [1].…”
Section: Introductionunclassified